Jogo da Partilha : relação entre ganho, perda e gênero - Silva, Fanny Silveira e (2015)
The Sharing Game, an economic game, studies behavior involved in resource allocation. The participant faces several trials in which he must choose between two options, both with an amount of resources for him and for other passive participant. In the optimal option the distributor receives more and the receiver even more, and in the non optimal option the distributor receives less and the other even less. From their choice, participants may be classified as optimizers, egalitarians or competitives. This work intends to assess whether and to what extent, distributions of strategies in the Sharing Game are affected by the variables gender distributor and allocation frame (gains or losses). There were the Experimental Conditions Gain-Loss and Loss-Gain, both involving hypothetical money. Data were collected online through the website Survey Monkey (n=427). In an intragroup analysis, there was no difference in the strategies adopted by participants distributing gains and losses. However, a between group analysis showed a significant order exposure effect of the allocation type, that is, if the game started with gains or losses. When comparing the two experimental conditions, the Gain-Loss condition presented an optimized strategy in a higher percentage of participants, and the Loss-Gain condition showed a higher percentage of participants both in the egalitarian and competitive strategies. Significant gender differences were found in the two experimental conditions, since in both of them the optimal strategy showed a higher percentage of men. This study has social and scientific importance by presenting an experimental model to study cooperation and competition. It also contributes for the economic games being more known and used in Psychology and Behavior Analysis. Finally, it provides greater generality to the data which may still be inconclusive regarding gender and the use of gains or losses in economic games.